The human subthalamic nucleus and globus pallidus internus differentially encode reward during action control. Issue 4 (28th January 2017) - Justin Rossi, Peter; Peden, Corinna; Castellanos, Oscar; Foote, Kelly D.; Gunduz, Aysegul; Okun, Michael S.
Abstract: The subthalamic nucleus (STN) and globus pallidus internus (GPi) have recently been shown to encode reward, but few studies have been performed in humans. We investigated STN and GPi encoding of reward and loss (i.e., valence) in humans with Parkinson's disease. To test the hypothesis that STN and GPi neurons would change their firing rate in response to reward‐ and loss‐related stimuli, we recorded the activity of individual neurons while participants performed a behavioral task. In the task, action choices were associated with potential rewarding, punitive, or neutral outcomes. We found that STN and GPi neurons encode valence‐related information during action control, but the proportion of valence‐responsive neurons was greater in the STN compared to the GPi. In the STN, reward‐related stimuli mobilized a greater proportion of neurons than loss‐related stimuli. We also found surprising limbic overlap with the sensorimotor regions in both the STN and GPi, and this overlap was greater than has been previously reported. These findings may help to explain alterations in limbic function that have been observed following deep brain stimulation therapy of the STN and GPi. Hum Brain Mapp 38:1952–1964, 2017 . ©2017 Wiley Periodicals, Inc.